Mental Health and Academic Performance of Private Senior High School Students in the Division of Zambales amid Pandemic - Basa, Webster B.; Abaniel, Arra Q. (Future Science / FSH-PH Publications, 2024)
This study aimed to assess the mental health of private senior high school students and its effect on their academic performance during the fourth quarter of S.Y. 2020−2021 amid pandemic. It was conducted among grade 11 students enrolled in private schools in Zone I, Division of Zambales utilizing an explanatory sequential mixed methods design. The Mental Health Inventory or MHI-38 was used as the questionnaire for the quantitative part while online interviews were used for qualitative part. Findings revealed that students experienced anxiety during the pandemic. Despite being anxious, students were psychologically well and less distressed. Overall, they were in a positive state of mental health. The study also revealed that students' anxiety has significant difference with the modular distance learning delivery modality. The study has found no significant relationship between students' mental health and academic performance during the last quarter of S.Y. 2020-2021. Qualitative data analysis found that students experienced mental, academic, and social problems during the pandemic.